The Influence Of Health Education Using Backsheets On Knowledge About Intra Uterine Device (IUD) Among Mothers At The Sukaraja Health Center Tasikmalaya District - Metty Nurherliyany; Indri Damayanti; Yanti Srinayanti; Yuyun Rahayu (INDOGENIUS, 2025)
Background & Objective :  Based on Indonesia's health profile (2022), IUD contraceptive users are 23,383, in West Java Province 8.04%, and in Tasikmalaya Regency 17,979 people, while in Sukaraja Community Health Center 907 people (19%). The low use of long-term contraception has several factors, one of the influencing factors is the lack of information provided to prospective family planning participants. By providing complete and sufficient information about IUD contraception, many prospective contraceptive participants understand and are not afraid to use IUD contraception. The aim of the research was to determine the effect of health education using flip sheets on knowledge about Intra Uterine Devices (IUD) among mothers at the Sukaraja Community Health Center, Tasikmalaya Regency.   Method: This research uses a type of quantitative research, namely quasi experimental design research with a one group pretest and posttest design. The population in this study was all 48 mothers at the Sukaraja Community Health Center who gave questionnaires before and after being given treatment. Result: Based on the results of research using the Wilcoxon test, it was found that the probability value of the sample experiencing an increase in knowledge about IUD contraception before and after being given health education was Asymp. Sig. (2-tailed) 0.000 < 0.05, then providing health education using flip sheets about IUD family planning to mothers has an influence on the level of knowledge. Conclusion: The conclusion from this research is that there is an influence on the level of knowledge in providing education.